Enhancing performance and sustainability of lithium manganese oxide cathodes with a poly(ionic liquid) binder and ionic liquid electrolyte - Ana Clara Rolandi; Nerea Casado; Anthony Somers; Iratxe de Meatza; David Mecerreyes; Cristina Pozo-Gonzalo; Patrick C. Howlett; Robert Kerr; Maria Forsyth (Journal of Power Sources Advances)
Current battery production involves various energy intensive processes and the use of volatile, flammable and/or toxic chemicals. This study explores the potential for using a water-soluble and functional binder, poly(diallyldimethylammonium) (PDADMA) with diethyl phosphate (DEP) as a counter anion, for lithium manganese oxide (LMO) cathodes. By replacing the traditional polyvinylidene fluoride (PVDF) binder and its associated toxic N-methyl-2-pyrrolidone (NMP) solvent, PDADMA-DEP offers a more sustainable and cost-effective solution. Notably, PDADMA-DEP electrodes do not require high-temperature calendaring to achieve high performance unlike PVDF electrodes. X-ray Photoelectron Spectroscopy (XPS) indicated significant interactions between the binder and LMO that enhance stability and ion conduction. The PDADMA-DEP binder demonstrated excellent electrochemical rate capability up to 10C with the conventional organic liquid electrolyte (LP30), outperforming PVDF electrodes. The performance of both binders using a safer and non-volatile ionic liquid electrolyte, specifically 50 mol% LiFSI in N-trimethyl-N-propylammonium bis(fluorosulfonyl)imide, was also investigated to enhance the overall safety and environmental impact of the battery system. IL-based cells utilizing a PDADMA-DEP cathode binder demonstrated a 58 % capacity retention over 500 cycles at 0.5C when cycled at room temperature.